KERAGAMAN DAN HERITABILITAS 10 GALUR INBRIDA S4 PADA TANAMAN JAGUNG KETAN (Zea mays L. var.ceritina Kulesh) - Reza Prakoso Dwi Julianto; Arifin Noor Sugiharto; Andy Soegianto (BUANA SAINS, 2016)
This research aims to determine the variability of S4 generation between waxy corn x local yellow corn (Arjuno) based on seed color selection and cob position. The research was conducted at Kelurahan Dadaprejo, Kecamatan Junrejo, Kota Batu with a height of ± 610 m asl, the maximum temperature is 27.4 º C and minimum temperature is 15.1 º C and with inceptisol type soil. The research started in December 2011 until March 2012. Plant materials that used here were 10 strains of S4 waxy corn from crossing with local corn (Arjuno) that have been selected based on seed color and cob location. This research used Randomized Design Group (RDG), three replications with 30 plants each genotype every replication by using one cob one line selection (ear to row). The results showed the character of plant height, the number of seed line, and the cob circumference among strains showed significant differences between inbred strains, The heritability values among strains showed medium value criteria in all parameters except the stalk length that showed the low heritability value